FIBRE OPTICS : Fabrication of microstructured optical fibres by drawing preforms sealed at their top end. (29th November 2016) - Denisov, A N; Kosolapov, A F; Senatorov, A K; Pal'tsev, P E; Semjonov, S L
Abstract: This paper presents results of a theoretical analysis and a series of experiments dealing with microstructured optical fibre (MOF) drawing from preforms sealed at their top end. We demonstrate that maintaining a constant temperature in the top part of the preform is of key importance for the ability to produce long MOFs with stable parameters. We have proposed and implemented a technique for additional, controlled heating of the top part of preforms, which allows one to fabricate long MOFs with both constant and varying parameters. Evidence is provided that MOFs with holes differing in size can be produced rather easily by this method.